Strategi Pembelajaran Berdiferensiasi dalam Pendidikan Pancasila di Sekolah Dasar: Tinjauan Literatur Sistematis - Riyadi, Diki; Rosiana Mufliva; Fitra Ramadhan; Silvi Fatimah Azhara Suherman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Differentiated learning is a learning approach that focuses on openness and freedom for students to meet their learning needs by providing different needs, interests and learning styles to students. Differentiated learning should be applied in all subjects in elementary schools, including Pancasila Education learning. The purpose of this study is to determine the extent of the development of differentiated learning in Pancasila Education subjects in elementary schools. This study is a literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The results of the study indicate that there have been many studies with similar topics, especially in elementary schools.